Impact of Friction Dampers on Seismic Performance: A Case Study of an Under-Designed Building Subjected to an Earthquake - Abdurrahman, Yusril; Wibowo, Ari; Zacoeb, Achfas (Rekayasa Sipil, 2025)
This study investigates the use of friction dampers to retrofit and enhance the seismic resilience of under-designed reinforced concrete buildings. A finite element model of a five-story reinforced concrete hospital, intentionally designed not to meet standard drift requirements, underwent nonlinear time history analysis. This analysis simulated two earthquake scenarios, with return periods of 225 (BSE-1E) and 975 (BSE-2E) years, considering soft soil conditions. The structure's seismic behavior was evaluated by analyzing key parameters such as base shear and inter-story drift ratio. The results showed that adding friction dampers significantly enhances the hospital's local and global structural performance in both earthquake scenarios. At the regional level, the dampers greatly decreased structural damage, eliminating plastic joints in the >CP category during the BSE-1E scenario and reducing them by up to 86.49% in the BSE-2E scenario. The dampers effectively reduced roof drift ratios at the global level, achieving a 45% reduction in the BSE-1E scenario. In the BSE-2E scenario, roof drift was kept below the Life Safety limit, with a 33.5% reduction. However, the dampers' effectiveness decreased as earthquake intensity increased, indicating limitations in their ability to manage scenarios beyond the initial design assumptions.